When Less or More Isn't Enough: Renal Maldevelopment Arising From Disequilibrium in the Renin-Angiotensin System - de Almeida, Lucas Ferreira; Coimbra, Terezila Machado (Frontiers in Pediatrics, 2019)
Environmental and nutritional factors during fetal and neonatal life can have long-lasting effects on renal functions and physiology and susceptibility to kidney disease in adulthood. All components of the renin-angiotensin system (RAS) are highly expressed in the kidneys during the period of renal development. The RAS plays a central role in the regulation of various cellular growth factors and stimulates adhesion molecules and cellular migration. The use of antagonists of this system during fetal development represents a major risk factor for hypertension, renal vascular dysfunction, and kidney medulla atrophy in adulthood. The inappropriate activation of the RAS by vitamin D (VitD) deficiency has been studied in recent years. Clinical and experimental studies have demonstrated an inverse relationship between circulating VitD levels and blood pressure, plasma and renin activity, and an increase in angiotensin II and the receptor AT1. These data raise new questions about the importance of the integrity of the RAS during development since RAS pathway inhibitors and VitD deficiency have opposing functions. This is a literature review on the possible mechanisms by which antagonists of the RAS and VitD deficiency during fetal development provoke disturbances in kidney structure and function. Potential mechanisms are presented and discussed, and the possible pathways by which an imbalanced maternal RAS may negatively impact fetal development and have consequences in adulthood are also explored.